THE STRATEGY OF ISLAMIC EDUCATION TO PREVENT RADICALISM: A CASE IN DIPONEGORO UNIVERSITY, INDONESIA - Arif Wibowo (Postgraduate Program, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The purpose of this research is to explore what are the strategies of Islamic Religious Education in countering radicalism at Diponegoro University. To analyze the factors supporting and inhibiting the strategy of Islamic Religious Education in countering radicalism at Diponegoro University. This type of research is qualitative with descriptive method. Data collection through: interviews, observation and documentation. The data analysis is descriptive with three paths, namely data reduction, data presentation, and drawing conclusions. The strategy implemented by Diponegoro University in counteracting radicalism is forming a special team to deal with anti-radicalism (TIMARU, in collaboration with existing stakeholders, establishing a comprehensive curriculum, strengthening lecture materials by holding public lectures/seminars/Forum Group Discussions on nationality and anti-radicalism, and channeling appropriate talents and interests through extracurricular activities. Factors that greatly support the success in implementing these strategies at Undip include, among others; adequate facilities and infrastructure, reliable human resources, good cooperation from all elements of the academic community, implementation of a comprehensive strategy and the existence of a technical team in countering radicalism, while several factors that are still hindering include: the lack of a technical team in the field, the existing regulations are too long and lengthy, and a hidden curriculum that is still not structured.